THE VIEW OF PATIENTS WITH CHORONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) ON COMPLEMENTARY AND ALTERNATIVE MEDICINE (CAM) IN EASTERN TURKEY - Şahin, Zümrüt Akgün; Şahin, Mutlu (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The purpose of this study was to examine the frequency of complementary and alternative medicine usage in Chronic Obstructive Pulmonary Disease (COPD) patients living in the eastern part of Turkey. In this study a descriptive design was used. The study was conducted with 216 patients who were present at the clinic. Data were gathered by the researchers in a comfortable setting through questionnaire method using the data collection form developed by the researcher. Individualised questionnaire-based interviews were also conducted among the 216 adult patients. The questionnaire included demographic information, clinical information, use of conventional therapies and complementary and alternative therapy. According to the findings obtained in this research, the frequency of CAM use among Turkish COPD patients (72.1%) was close to the highest levels reported in the literature.